2012
DOI: 10.1094/mpmi-09-11-0253
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescensInduces Strain-Dependent and Strain-Independent Host Plant Responses in Defense Networks, Primary Metabolism, Photosynthesis, and Fitness

Abstract: Colonization of plants by nonpathogenic Pseudomonas fluorescens strains can confer enhanced defense capacity against a broad spectrum of pathogens. Few studies, however, have linked defense pathway regulation to primary metabolism and physiology. In this study, physiological data, metabolites, and transcript profiles are integrated to elucidate how molecular networks initiated at the root-microbe interface influence shoot metabolism and whole-plant performance. Experiments with Arabidopsis thaliana were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 80 publications
3
106
0
Order By: Relevance
“…Total RNA was isolated, DNase treated and checked for quality using an Experion RNA StdSens analysis kit and chip (BioRad) as described in (Weston et al 2012). cDNA was synthesized using a SuperScript III First-Strand Synthesis SuperMix for qRT-PCR (Invitrogen) according to provided protocols.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated, DNase treated and checked for quality using an Experion RNA StdSens analysis kit and chip (BioRad) as described in (Weston et al 2012). cDNA was synthesized using a SuperScript III First-Strand Synthesis SuperMix for qRT-PCR (Invitrogen) according to provided protocols.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…One hypothesis is that leaf endophytes reduce disease severity by priming plant resistance to pathogens, as has been shown for rhizobacteria and mycorrhizal fungi (Wang et al 2005, Weston et al 2012. The idea of plant symbionts as ''vaccines'' was first suggested long ago (Beauv- v www.esajournals.org erie 1901), and is now referred to as systemic acquired resistance (SAR) or induced systemic resistance (ISR; Van Wees et al 2008).…”
Section: Direct Versus Indirect Interaction Hypothesesmentioning
confidence: 99%
“…To date, there is little information available on metabolic changes induced in plants by PGPR that enhance resistance against pathogens or insect pests (Walker et al, 2011;Weston et al, 2012). Furthermore, for only few rhizobacterial strains, transcriptomic analyses have been conducted to unravel the molecular changes in plants associated with induced systemic resistance (Cartieaux et al, 2003(Cartieaux et al, , 2008Verhagen et al, 2004;Wang et al, 2005;Weston et al, 2012).…”
mentioning
confidence: 99%
“…Furthermore, for only few rhizobacterial strains, transcriptomic analyses have been conducted to unravel the molecular changes in plants associated with induced systemic resistance (Cartieaux et al, 2003(Cartieaux et al, , 2008Verhagen et al, 2004;Wang et al, 2005;Weston et al, 2012). Almost all of these microarray studies revealed relatively few transcriptional changes: for instance, plant-growth promoting Pseudomonas thivervalensis strain MLG45 induced transcriptional changes in 63 genes in the shoots and in nine genes in the roots of Arabidopsis (Arabidopsis thaliana), with an increase in defense-related transcripts and a repression of photosynthesis-related genes (Cartieaux et al, 2003).…”
mentioning
confidence: 99%
“…For instance, P. fluorescens bacteria are able to use a broad range of nutritional sources, producing high-affinity Fe +3 binding siderophores, thus restricting the growth of other rhizosphere bacteria under conditions of low iron concentrations. They can also remain viable for long periods of time under very adverse conditions, making them suitable as biofertilizers (Weston et al, 2012).…”
Section: Introductionmentioning
confidence: 99%